Genomic insights into Aspergillus sydowii 29R-4-F02: unraveling adaptive mechanisms in subseafloor coal-bearing sediment environments - Jiang, Jun-Peng; Liu, Xuan; Liao, Yi-Fan; Shan, Jun; Zhu, Yu-Ping; Liu, Chang-Hong (Frontiers in Microbiology, 2023)
Aspergillus sydowii is an important filamentous fungal species that inhabits diverse environments. However, investigations on the biology and genetics of A. sydowii in subseafloor sediments remain limited. Here, we performed de novo sequencing and assembly of the A. sydowii 29R-4-F02 genome, an isolate obtained from approximately 2.4 km deep, 20-million-year-old coal-bearing sediments beneath the seafloor by employing the Nanopore sequencing platform. The generated genome was 37.19 Mb with GC content of 50.05%. The final assembly consisted of 11 contigs with N50 of 4.6 Mb, encoding 12,488 putative genes. Notably, the subseafloor strain 29R-4-F02 showed a higher number of carbohydrate-active enzymes (CAZymes) and distinct genes related to vesicular fusion and autophagy compared to the terrestrial strain CBS593.65. Furthermore, 257 positively selected genes, including those involved in DNA repair and CAZymes were identified in subseafloor strain 29R-4-F02. These findings suggest that A. sydowii possesses a unique genetic repertoire enabling its survival in the extreme subseafloor environments over tens of millions of years.